PsycTESTS Dataset 2016
DOI: 10.1037/t58979-000
|View full text |Cite
|
Sign up to set email alerts
|

Moral Disengagement in Doping Scale

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…In line with Bandura's (1991) theory of moral thought and action and in agreement with past research (Engelberg et al, 2015;Hodge, et al, 2013;Kavussanu et al, 2016;Mallia, et al, 2016;Ring & Kavussanu, 2017;Zelli, et al, 2010Zelli, et al, , 2016, we found that moral disengagement was linked with a permissive view of doping, with athletes who had the PROJECTED DOPING tendency to morally disengage, also being most likely to consider doping. Importantly, the moral disengagement-doping relationship was influenced by the context, with a mediumsized positive effect for benefit situations and a small-sized positive effect for cost situations.…”
Section: A Moral Framework For Dopingsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with Bandura's (1991) theory of moral thought and action and in agreement with past research (Engelberg et al, 2015;Hodge, et al, 2013;Kavussanu et al, 2016;Mallia, et al, 2016;Ring & Kavussanu, 2017;Zelli, et al, 2010Zelli, et al, , 2016, we found that moral disengagement was linked with a permissive view of doping, with athletes who had the PROJECTED DOPING tendency to morally disengage, also being most likely to consider doping. Importantly, the moral disengagement-doping relationship was influenced by the context, with a mediumsized positive effect for benefit situations and a small-sized positive effect for cost situations.…”
Section: A Moral Framework For Dopingsupporting
confidence: 91%
“…They are able to do so by disengaging moral self-sanctions (i.e., guilt, shame) from reprehensible behavior by enacting a thought process -termed moral disengagement -that allows individuals with the same moral standards to act differently in the same situation (Bandura, 1991). Mechanisms of moral disengagement have been identified in relation to doping, with many studies linking moral disengagement with increased intention or likelihood of doping in sport (e.g., Engelberg et al, 2015;Hodge, Hargreaves, Gerrard, & Lonsdale, 2013;Kavussanu et al, 2016;Lucidi et al, 2004;2008;Mallia et al, 2016;Ring & Kavussanu, 2017).…”
Section: Social Cognitive Theory and Doping 23mentioning
confidence: 99%
See 3 more Smart Citations